POLITIK KRIMINAL PENANGGULANGAN PENIPUAN ONLINE PADA TRANSAKSI E-COMMERCE MELALUI MEDIA SOSIAL - Muhammad Hafiz Alfaiz Ramadhan (2022)
Throughout January 2020 to October 2021, the number of public complaints related to cyber crimes reached 2,259 cases. Of these numbers, not all cases have been resolved. Only 527 cases were successfully resolved by the police. This study aims to determine the factors that cause delays in the completion of online fraud cases and to find out penal and non-penal efforts to overcome online fraud using social media. This research was conducted using a normative legal research method through a literature study which was complemented by interviews. The results of the study can be concluded that the obstacles in solving online fraud cases are caused by several factors, namely the inequality of facilities and infrastructure owned by the police, human resources that are lacking in number and capability, and the lack of evidence. Then one form of penal effort taken to tackle online fraud is law enforcement with laws and regulations governing fraud which have been regulated in the Criminal Law, the ITE Law, and the Consumer Protection Law. Then forms of non-penal efforts can be carried out by conducting outreach and debriefing to the community, leveling the budget as well as facilities and infrastructure for the police that can support the resolution of online fraud cases, and providing training to special police units for cyber crimes.